Ginsenoside Rg3 Mitigates Atherosclerosis Progression in Diabetic apoE–/– Mice by Skewing Macrophages to the M2 Phenotype - Guo, Mengqi; Xiao, Jie; Sheng, Xi; Zhang, Xinyu; Tie, Yuanyuan; Wang, Lei; Zhao, Lang; Ji, Xiaoping (Frontiers in Pharmacology, 2018)
Abstract Atherosclerosis (AS) in diabetic patients is often associated with low stability, which might be largely attributed to unfavourable macrophage polarization and increased inflammatory response induced by hyperglycaemia. Ginsenoside Rg3 is one of the main active principles of Panax Ginseng, which has been reported to be a natural ligand of peroxisome proliferator-activated receptor-gamma (PPARγ), a key nuclear transcriptional factor involved in inflammation and macrophage differentiation. However, it remains unclear if Rg3 could exert protective effects on plaque stability in diabetes. In this study, we investigated the role of ginsenoside 20(S)-Rg3 in macrophage polarization and AS plaque stability using advanced glycation end products-treated macrophages and diabetic AS mice models. In vitro, advanced glycation end products (AGEs) treatment promoted the expression of proinflammatory molecules and M1 surface markers, whereas 20(S)-Rg3 could reverse the M1 polarization to the M2 phenotype. In vivo, the administration of 20(S)-Rg3 promoted AS lesion stability and reduced the plaque burden, accompanied by increased M2 macrophages and reduced M1 macrophages. In addition, PPARγ antagonist GW9662 co-administration mostly blocked these effects, suggesting the important role of PPARγ pathways in mediating 20(S)-Rg3 effects in macrophage polarization and atherosclerosis progression. Together, these results demonstrated an immunomodulatory role of ginsenoside 20(S)-Rg3 in promoting macrophages to a profile of the M2 typethrough PPARγ-dependent mechanisms, and indicated a potential role of 20(S)-Rg3 in the prevention and treatment of diabetic atherosclerosis.